Effects of Science Augmented Reality Learning Media on Student Learning Outcomes: A Meta Analysis - Anzuye, Ivo Jihan; Asrizal, Asrizal; Amir, Harman; Riyasni, Selma (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The background of this research is the inconsistency of findings in various previous studies regarding the effectiveness of Augmented Reality (AR) in improving learning outcomes. This study aims to analyze the influence of Augmented Reality (AR) learning media on student learning outcomes in the subject of Science through meta-analysis methods. The type of research used is this meta-analysis conducted on 38 relevant articles published between 2013 and 2024, selected based on PICOS inclusion criteria. The analysis used effect size calculations and statistical tests using the JASP application. The results showed that AR had a strong and significant effect on student learning outcomes. The findings also revealed that the strongest effect appeared in elementary school students, especially in physics material and on the aspect of knowledge and critical thinking skills. These results indicate that AR-based learning media is highly effective in improving conceptual understanding and cognitive engagement in science learning. abstract should be clear, concise, and descriptive.